Climate change, gender, and nutrition linkages: Research priorities for Bangladesh - De Pinto, Alessandro; Meinzen-Dick, Ruth S.; Choufani, Jowel; Theis, Sophie; Bhandary, Prapti (International Food Policy Research Institute, 2017)
Climate change, coupled with high levels of poverty and population density, is a substantial threat to sustainable development in Bangladesh. Climate-related threats, such as flooding, inundation, salt-water intrusion, and changes in temperatures are increasing with climate change. Achieving the goals of Feed the Future and the Global Food Security Strategy requires careful consideration of the impact of relevant climate science on agricultural production, while at the same time considering other cross-cutting issues that influence agricultural growth, poverty alleviation, and resilience—especially gender and nutrition. This policy note summarizes assessments of these linkages in Bangladesh under the Gender, Climate Change, and Nutrition Integration Initiative (GCAN).